2011
DOI: 10.1007/s00181-011-0455-2
|View full text |Cite
|
Sign up to set email alerts
|

Does domestic financial development enhance the linkages between foreign direct investment and economic growth?

Abstract: The study examines the relationship between foreign direct investment (FDI), financial development, and economic growth in a panel of 95 developed and developing countries from 1983 to 2006. The study moves away from the traditional cross-sectional analysis, and focuses on more direct evidence of the channels via which FDI might help or retard economic growth. Using generalized method of moment (GMM) panel data analysis, we find strong evidence of a positive relationship between FDI inflows into a country and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 69 publications
5
28
0
4
Order By: Relevance
“…However, he also observed that high human capital low-income countries benefit more from FDI than others (cf. Choong, 2012).…”
mentioning
confidence: 99%
“…However, he also observed that high human capital low-income countries benefit more from FDI than others (cf. Choong, 2012).…”
mentioning
confidence: 99%
“…Keputusan terma interaksi ini mencadangkan bahawa kualiti pembangunan pasaran saham adalah pra-syarat yang penting bagi FDI untuk mengeluarkan kesan positif kepada pertumbuhan ekonomi. Dapatan ini adalah selaras dengan hasil kajian terdahulu bahawa kesan FDI kepada pertumbuhan adalah bergantung kepada kapasiti penyerapan negara penerima (lihat contoh, Hermes & Lensink 2003;Alfaro et al 2004;Azman-Saini et al 2010a;Choong 2012; antara lain). Justeru, dapatan kajian ini menekankan bahawa sebagai tambahan kepada dimensi kuantitatif yang kini ditumpukan dalam pembangunan kewangan, dimensi kualiti pembangunan kewangan juga merupakan elemen penting dalam hubungan FDI-pertumbuhan ekonomi.…”
Section: Kesimpulanunclassified
“…Secara kolektif, kajian-kajian empirikal yang baru yang menyiasat peranan pembangunan kewangan dalam hubungan FDI-pertumbuhan ekonomi, menunjukkan pembangunan kewangan adalah penting untuk negara mendapatkan kesan pertumbuhan daripada FDI (lihat, untuk contoh Hermes & Lensink 2003;Lee & Chang 2009;Azman-Saini et al 2010a;Choong 2012). Hermes dan Lensink (2003) mendapati bahawa pembangunan bank dan pasaran saham adalah prasyarat penting bagi limpahan FDI untuk direalisasikan secara positif.…”
unclassified
See 1 more Smart Citation
“…However, on multiple national levels, Alfaro et al, Niels and Lensink, and Choong et al concentrated on comparative studies between developed and undeveloped countries regarding financial market development under the effects of FDI spillovers. They revealed that countries with well-developed financial markets usually gained significant spillovers from FDI, and that FDI generated a negative effect on countries with poor financial markets [57,64,65]. Furthermore, Li and Zeng, Su and Song, and Luo also carried out comparative studies, but focused on the different financial market development phases.…”
Section: Introductionmentioning
confidence: 99%